Alarm System and Emergency Message from Wheelchair User Emergency Condition - Yavez. E. Loho; Diana Lestariningsih; Peter R Angka (International Journal of Applied Sciences and Smart Technologies, 2021)
When someone uses a wheelchair, there is still the possibility of an accident to the user, such as when the user suddenly falls down from the wheelchair or the user falls down along with the wheelchair. For notification of emergency conditions for wheelchair users, an alarm system is designed that can send messages to the intended mobile number. The system is designed using Wemos D1 mini, Ultrasonic, MPU-6050 and Proximity E18-D80NK sensors. The conclusion from the measurement and test results are: the value read by the MPU-6050 sensor is taken one axis for each direction when the wheelchair was falling down, Y≤180o for left falling down, X≤50o for right falling down, Z≤65o for forward falling and  Z≥140o for backwards falling down. The Ultrasonic sensor works well for detecting the presence of user’s legs and the E18-D80NK proximity sensor works well for detecting the position of the user who is sitting in a wheelchair. Receiving notifications through the BLYNK server works well, not affected by distance provided there is an internet connection connected to the device.